ANALISIS SPASIAL DAERAH RAWAN BANJIR DI DAS WAE HERU, KOTA AMBON - Heinrich Rakuasa; Philia Christi Latue (Jurnal Tanah dan Sumberdaya Lahan, 2023)
The intensity of the high rainfall resulted in the overflow of the Wae Heru watershed, which resulted in a catastrophic flood that hit residential areas around the watershed. This study aimed to analyze spatially the level of flood hazard and its exposure to settlements in the Wae Heru watershed, Ambon City. This research used overlay technique, scoring method and weighting using ArcMap 10.8 software as a Geographic Information System (GIS) based approach. The variables used included rainfall, elevation, slope, soil type, land cover and distance from the river. The results showed that the flood hazard level was dominated by a low hazard level of 361.28 ha and the flood exposure level in settlements was dominated by a high hazard area of 54.68 ha. The results of the study are expected to be useful in flood mitigation efforts to minimize losses, both fatalities and physical damage.